Relasi Islam, Negara, dan Kekuasaan: Dinamika Politik Pemerintahan Era Kenabian hingga Negara Bangsa di Nusantara - Ica Maitasa (Jurnal Global Futuristik, 2026)
The fundamental discourse concerning the architectural relationship between Islam, state entities, and power mechanisms constitutes an academic subject that consistently occupies a central position within political historiography and the sociology of the state. This comprehensive research aims to dissect and profoundly reconstruct the evolution of the political dynamics of Islamic governance. The study traces the historical timeline from the formative phase of the prophetic era, shifting towards the monarchical forms of major dynasties, traversing the power acculturation of the Malay-Nusantara Sultanates, until finally crystallizing into a structural transformation towards the modern nation-state. The analytical approach is focused on the epicenter of the Nusantara region, where the convergence of orthodox Islamic doctrines and local wisdom engendered a distinct variant of governance, prioritizing the principles of social harmony and cultural accommodation. The findings indicate that the relationship between religion and the state has never operated within a static vacuum; conversely, these entities continually undergo a historical dialectical process profoundly influenced by the determinants of social structure, political-economic rationality, and disruptions stemming from colonial intervention. In the contemporary era, the political articulation of Islam demonstrates a high degree of resilience, manifested through the emergence of Civil Islam in Indonesia and the polarization of ethno-religious identity-based political structures in Malaysia, representing two divergent pathways in state governance. In conclusion, the Islamic political paradigm in this region has successfully achieved a hybridization between adherence to transcendental divine values and the implementation of democratic, inclusive, and pluralistic governance principles.